UJI DAYA TERIMA REMPEYEK KACANG HIJAU YANG DIMODIFIKASI DENGAN TEPUNG BELALANG KAYU (Melanoplus cinereus) - Liza Meilida Nasution; Jumirah .; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Wood locust (Melanoplus cinereus) have only utilized a small portion of society with fried and served with warm rice when the protein content is very high. Wood locust flour can be used as ingredient in making peanut brittle to increase the nutrient content in it. Peanut brittle is a snack highly appreciated by the public. This research purpose to determine the acceptability test of peanut brittle green beans modified with the wood lacust flour. The type of research was an experiment conducted by completely randomized design using three factors and with three treatments, the treatmens are the addition of rice flour, locust flour and tapioca flour with treatments A1 (60%: 20%: 20%), A2 (60%: 25%: 15%), A3 ( 60%: 30%: 10%). The acceptability carried out on 30 panelists from Public Health Faculty. The results organoleptic test based on color, aroma and taste the most preferred is a peanut brittle with a mixture of locust wood flour 20% and tapioca flour20%. While the results of organoleptic test against the most preferred texture is peanut brittle with a mixture of locust wood flour 30% and tapioca flour 10%. Based on the analysis of variance, peanut brittle green beans locust flour modified with various levels of comparison gives a significantly different effect on the color, aroma and flavor. As for the texture characteristics do not give a significantly different effect on the resulting peanut brittle. It is recommended that peanut brittle green beans with modified wood locust flour can be used as a snack food on children or families because the cost of making is classified as cheap and can contribute to the protein that is large enough from the needs of daily to prevent protein deficiency. Keywords: Wood Locust Flour, Brittle, Acceptability